Pengaruh Motivasi dan Disiplin Kerja terhadap Semangat Kerja Karyawan PT. Bineatama Kayone Lestari Tasikmalaya - Meita Dita Suryana; Cece Rakhmat; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of motivation and work discipline on employee morale at PT. Bineatama Kayone Lestari. This type of research is a quantitative research with a survey approach method. The population in this study are all employees of PT. Bineatama Kayone Lestari totaling 1,240 employees and samples taken as many as 95 respondents. The analytical tool used is multiple linear regression analysis, with hypothesis testing, namely the F test and t test. The results of the study based on the F test showed that motivation and work discipline simultaneously had a significant effect on employee morale. Based on the t test, it shows that motivation partially has a significant effect on morale and work discipline partially has a significant effect on work morale.